2004
DOI: 10.4141/p03-164
|View full text |Cite
|
Sign up to set email alerts
|

The value of apple characteristics to wholesalers in western Canada: A hedonic approach

Abstract: The value of apple characteristics to wholesalers in western Canada: A Hedonic approach. Can. J. Plant Sci. 84: 829-835. Sensory methods have been used to evaluate subjective apple characteristics such as juiciness, flavour, and texture. There is very little information to indicate the value wholesalers place on objective apple characteristics such as cultivar, grade, and fruit size. In this study, a hedonic price function for apples was estimated to evaluate the relationship between British Columbia (BC) appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Determining the implicit contribution of the various grain quality attributes to the market price of rice varieties can be done through hedonic pricing analysis [ 37 ]. Hedonic pricing regressions have been quite popular in the economics literature, being applied to various food commodities such as wine [ 38 , 39 ], tea [ 40 ], apples [ 41 ], and breakfast cereals [ 42 ]. In all these commodities, the products could be grouped into quality classes or varieties [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Determining the implicit contribution of the various grain quality attributes to the market price of rice varieties can be done through hedonic pricing analysis [ 37 ]. Hedonic pricing regressions have been quite popular in the economics literature, being applied to various food commodities such as wine [ 38 , 39 ], tea [ 40 ], apples [ 41 ], and breakfast cereals [ 42 ]. In all these commodities, the products could be grouped into quality classes or varieties [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers prefer large, visually appealing fruit [32,33], so selection for large fruit size may explain our observation. We also found that cultivated apples are 43% less acidic than wild counterparts.…”
Section: Discussionmentioning
confidence: 85%
“…Some products of this sector that have been studied by this method are breakfast cereals (Morgan et al, 1979;Stanley and Tschirhart, 1991;Shi and Price, 1998), the aquaculture industry (McConnell and Strand, 2000;Carroll et al, 2001), apples (Tronstad et al, 1992;Carew, 2000;Carew and Smith, 2004;Troncoso and Aguirre, 2007), organic tomatoes (Huang and Lin, 2007), avocados (Troncoso et al, 2008), beef (Unnevehr and Bard, 1993;Wahl et al, 1995;Loureiro and McCluskey, 2000;Boland and Schroeder, 2002;Gracia and Pérez, 2004), and pork (Parcell and Schroeder, 2007).…”
Section: Market Valuesmentioning
confidence: 99%